O tráfico de escravos nas relações externas de Brasil e de Portugal: 1822 a 1850 - Silva, Leonardo Bruno [UNESP] (2014)
The present thesis is focused on the traffic of slaves to Brazil, from the Portuguese colonies in Africa, seen here by the international relations undertaken by Portugal and Brazil from 1822 to 1850. It tries to understand how the internal political dynamics of these two nations were essential for the establishment of their foreign policies in regard of the africans slave trade. The relations undertaken between Brazil, Portugal and England form the structural axis of analysis, which concludes the fundamental importance of local political actions for the suppression of the slave traffic